2022
DOI: 10.2298/yjor210915005m
|View full text |Cite
|
Sign up to set email alerts
|

Tauberian theorems for weighted means of double sequences in intuitionistic fuzzy normed spaces

Abstract: We define weighted mean summability method of double sequences in intuitionistic fuzzy normed spaces(IFNS), and obtain necessary and sufficient Tauberian conditions under which convergence of double sequences in IFNS follows from their weighted mean summability. This study reveals also Tauberian results for some known summation methods in the special cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Among these initiatives are the development of smart and AI-based devices to lessen stress (Jung & Yoon, 2017) in smart cities (Falco et al, 2018), AI practitioners' predictions of job displacement (Gruetzemacher et al, 2020) estimation of the rate of depression among workers using the Apriori algorithm, and forecasts of the susceptibility of occupations to computerization in the near future (Jena & Kamila, 2014). Mishra et al (2022) revealed that the results generated from the Tauberian conditions by the convergence of a dual sequenced intuitionistic fuzzy normed spaces (IFNS) are significant for obtaining the weighted mean of computed nodes in some special cases. The development of a neuro-fuzzybased model that can automatically predict task performance and fitness rate with accuracy comparison checks on three (3) machine learning models is our key addition to this body of knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these initiatives are the development of smart and AI-based devices to lessen stress (Jung & Yoon, 2017) in smart cities (Falco et al, 2018), AI practitioners' predictions of job displacement (Gruetzemacher et al, 2020) estimation of the rate of depression among workers using the Apriori algorithm, and forecasts of the susceptibility of occupations to computerization in the near future (Jena & Kamila, 2014). Mishra et al (2022) revealed that the results generated from the Tauberian conditions by the convergence of a dual sequenced intuitionistic fuzzy normed spaces (IFNS) are significant for obtaining the weighted mean of computed nodes in some special cases. The development of a neuro-fuzzybased model that can automatically predict task performance and fitness rate with accuracy comparison checks on three (3) machine learning models is our key addition to this body of knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…fuzzy sets [ 17 , 23 ], approximation theory [ 24 26 ] etc. Intuitionistic fuzzy sets (IFS) was introduced by [ 27 ] to assign non membership grades and it was studied by [ 28 , 29 ]. Neutrosophic fuzzy set (NFS) was introduced in 1998 by [ 30 ] to assign incomplete, indeterminate, and inconsistent information.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Chandra, Srivastava, and Sinha [6]; Srivastava, Sinha and Chandra [17] introduced 2-norm and 2-inner product on fuzzy linear spaces over fuzzy field. For more recent work of the area under study, we refer to [7,12,13,14,15,16]. In the present paper we introduce the idea of anti-norm and anti-inner product function on anti-fuzzy linear space over anti-fuzzy field and also given fuzzy continuous and fuzzy bounded linear operators on anti-fuzzy linear space over anti-fuzzy field.…”
Section: Introductionmentioning
confidence: 99%